AN UPDATED CHECKLIST AND A NEW SPECIES OF BEGONIA (B. RHEOPHYTICA) FROM MYANMAR - Hughes, M.; Aung, M. M.; Armstrong, K. (Edinburgh Journal of Botany, 2019)
A new species, Begonia rheophytica (§ Platycentrum), is described from northern Myanmar; it was initially confused with B. rhoephila, which is confined to Peninsular Malaysia. Comparison with other species with a rheophytic leaf shape is made. This new addition brings the number of currently recognised Begonia species in Myanmar to 73. An updated checklist of Myanmar Begonia species is also included.
Keywords: Biodiversity; Hkakaborazi National Park; Kachin State; Myanmar; taxonomy